Influence of parallel magnetic field on cyclotron mass in double-layer two-dimensional electron system - Takaoka, S.; Kuriyama, A.; Oto, K.; Murase, K.; Cukr, M.; Jungwirth, T.; Smrcka, L. (Microelectronic engineering, 1999)
The cyclotron resonance of the double-layer two-dimensional electron system in tilted magnetic fields is investigated with the far-infrared Fourier spectrometer. We measure the parallel magnetic field ( B |) dependence of cyclotron mass due to the distortion of the “Fermi loop” by B |.